2015
DOI: 10.1213/ane.0000000000000912
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of Patients with Congenital Insensitivity to Pain with Anhidrosis

Abstract: BACKGROUND Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive disorder characterized by recurrent episodic fevers, anhidrosis, absent reaction to noxious stimuli, self-mutilating behavior, and mental retardation. The anesthetic management of patients with CIPA is challenging. Autonomic nervous system abnormalities are common, and patients are at increased risk for perioperative complications. METHODS In this study, we describe our experience with 35 patients with CIPA who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Zlotnik et al [14] examined 358 operations performed under general anesthesia in 35 CIPA patients. The ratio of the anesthetic agents used in these operations was; thiopental 4%, ketamine 27%, propofol 71%, opioid 8%, muscle relaxants 27%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zlotnik et al [14] examined 358 operations performed under general anesthesia in 35 CIPA patients. The ratio of the anesthetic agents used in these operations was; thiopental 4%, ketamine 27%, propofol 71%, opioid 8%, muscle relaxants 27%.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, bispectral index (BIS) monitoring was used to evaluate the depth of anesthesia. [13][14] We could not monitor the BIS because the conditions in our clinic were not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…These physiological responses occur because these cranial nerves are intact in patients with CIPA. A previous study showed that tachycardia within 10 minutes after induction occurred in 31% of CIPA patients and that the patients could respond to airway manipulation [ 13 ]. Intraoperative bradycardia was also observed in 2.8% of CIPA cases [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that tachycardia within 10 minutes after induction occurred in 31% of CIPA patients and that the patients could respond to airway manipulation [ 13 ]. Intraoperative bradycardia was also observed in 2.8% of CIPA cases [ 13 ]. In pediatric patients, cardiovascular complications were reported to be common [ 3 ] and to sometimes induce hemodynamic change by an unpleasant sensation [ 3 , 14 ]; therefore, attention should be paid to hemodynamics in patients with CIPA, even if a compensatory response is present.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients with CIPA are susceptible to numerous anesthetic complications due to autonomic abnormalities, including hemodynamic instability, particularly hypotension, bradycardia, and hyperthermia [ 4 ]. Due to the rarity of CIPA, anesthesia management experience is limited, with previous reports describing cases of orthopedic, maxillofacial, or debridement surgery associated with disease-related trauma [ 5 ]. Here, we describe the anesthetic management of young twins with CIPA who underwent airway surgery (adenotonsillectomy) unrelated to the conditions underlying CIPA, which is normally associated with a stress response.…”
Section: Introductionmentioning
confidence: 99%